b-Metric Like Spaces: A Survey of Concepts and Applications - Moussaoui, Abdelhamid (Vojnotehnički glasnik / Military Technical Courier, 2025)
This paper provides a comprehensive survey of fixed point results in metric-like spaces, with a particular focus on b-metric-like spaces. The notion of b-metric-like spaces generalizes several important concepts, including partial metric spaces, metric-like spaces, and b-metric spaces. The paper highlights significant contributions from the early stages of research to the present, offering an extensive compilation of foundational and recent results. Finally, we provide affirmative answers to some open problems arising from best proximity results in orthogonal 0-complete b-metric-like spaces, further advancing the understanding of fixed point theory in these generalized settings. This survey aims to equip researchers with valuable insights and references, facilitating further exploration and development in the study of metric-like spaces and their generalizations.